Kebijaksanaan Nabi Muhammad Pada Perjanjian Hudaibiyah: Inspirasi Ulama Indonesia Dalam Penghapusan 7 Kata Piagam Jakarta - Muttaqiin, Zainal (Al-Makrifat: jurnal kajian Islam, 2024)
This research aims to examine the wisdom of Prophet Muhammad in the Treaty of Hudaibiyah and to connect it with the inspiration drawn by Indonesian scholars in the removal of seven words from the Jakarta Charter in 1945. The methodology employed in this study is a library research approach, which allows for the analysis and comparison of both events. Through an in-depth analysis, this study finds that the Treaty of Hudaibiyah exemplifies Prophet Muhammad’s wisdom in confronting seemingly unjust political demands while strategically benefiting the Muslim community in the future. Similarly, the removal of seven words from the Jakarta Charter by Indonesian scholars demonstrates the application of the same principles in maintaining national unity amidst Indonesia’s religious pluralism. This research provides new insights into understanding the relevance of diplomatic values and the wisdom of Muslim leaders in the context of Islamic history and Indonesia’s independence. Keywords: Treaty of Hudaibiyah, Jakarta Charter